2014
DOI: 10.1007/s00404-014-3190-z
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of long-term effects of percutaneous tibial nerve stimulation on chronic pelvic pain

Abstract: PTNS is a minimally invasive treatment method that leads to decrease in pain severity and improvement in quality of life in women with chronic pelvic pain with effects continuing at 6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 27 publications
0
35
0
Order By: Relevance
“…Asintravesical Bacillus-Calmette Guerin BCG instillations failed to show a significant response rate in terms of LUTS related QoL, this treatment has largely fallen out of favor in the treatment of IC [32] , [33] . Studies are also lacking regarding QoL with chondroitin sulfate and hyaluronic acid [34] , [35] . Larger scale studies and placebo-control studies will be needed to assess these results.…”
Section: Qol After Treatmentmentioning
confidence: 99%
“…Asintravesical Bacillus-Calmette Guerin BCG instillations failed to show a significant response rate in terms of LUTS related QoL, this treatment has largely fallen out of favor in the treatment of IC [32] , [33] . Studies are also lacking regarding QoL with chondroitin sulfate and hyaluronic acid [34] , [35] . Larger scale studies and placebo-control studies will be needed to assess these results.…”
Section: Qol After Treatmentmentioning
confidence: 99%
“…155,158,159 PTNS has also been demonstrated to decrease chronic pelvic pain. [160][161][162] The remote effects of posterior tibial NS are analogous to remote segmental analgesia in chronic pain.…”
Section: Remote Effects Of Nerve Stimulation In Nonpain Applicationsmentioning
confidence: 99%
“…[41] Another study demonstrated that pain complaints of patients with chronic prostatitis/CPP significantly reduced with electroacupuncture. [42] Istek et al [43] studied 33 women with CPP randomly assigned to either percutaneous tibial nerve stimulation (PTNS) or control. A total of 30-min PTNS for three days per week were applied for 12 weeks.…”
Section: Physiotherapy and Rehabilitationmentioning
confidence: 99%